Grupy szczególnie zagrożone wykluczeniem społecznym — aspekt demograficzny - Rauziński, Robert; Sołdra-Gwiżdż, Teresa; Szczygielski, Kazimierz (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Groups particularly in risk of social exclusion — a demographic aspect The paper deals with groups that are in particular danger of social exclusion (about 30% of the country’s population): structural (incomes below the poverty level, unemployment, homelessness), physical (disability, chronic disease), normative (related to breaking the law, social pathology). In the light of the demographic-statistical research in Opole Region, it is possible to distinguish seven groups especially endangered with social exclusion. Special attention should be paid to wage-earning emigrants and their children with weakened family and social bonds (“Euro-orphans”) in connection with the increase in migration processes in the Region. A decisive factor limiting the problem of availability of work and the danger of social exclusion is an economic boom in the region. Key words: risk of social exclusion, wage-earnig emigrants, migration processes, availability of work economic boom